Pengaruh Literasi dengan Model Inquiry Terbimbing dalam Melatihkan Keterampilan Proses Sains Siswa di MI Roudlotul Falah - Novaria Lailatul Jannah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2021)
Literacy is the ability to access, understand, and use something intelligently through various activities or activities, including reading, seeing, listening, writing and speaking. Science Process Skills (KPS) is a learning approach oriented to science learning. This study aims to study the Effect of Literacy and inquiry proces on Science Process Skills of Students at MI Roudlotul Falah Kalisat District of Rembang, Pasuruan Regency. This type of research is a quantitative approach. The type of research approach is descriptive quantitative, namely research to give a description of the symptoms, phenomena, or facts examined by describing the value of independent variables, without intending to connect or compare. Data collection methods used in this study were observation, interviews, documentation and questionnaires. From the results of the study, the Influence of Literacy and inquiry proces on the development of Science Process Skill Students have a value of 78.190%, thus the variable shows sufficient category. This means demonstrating that Literacy Against the Development of Science Process Skill is quite influential for Students at MI Roudlotul Falah.